Alopecia Universalis following Alemtuzumab Treatment in Multiple Sclerosis: A Barely Recognized Manifestation of Secondary Autoimmunity—Report of a Case and Review of the Literature - Zimmermann, Julian; Buhl, Timo; Müller, Marcus (Frontiers in Neurology, 2017)
Secondary autoimmunity is the most frequent adverse event occurring in almost every other alemtuzumab-treated MS-patient. We report a case of a patient with relapsing-remitting multiple sclerosis who reported smooth, circular areas of complete hair loss on both thighs six months after the second treatment cycle with alemtuzumab. The patient was diagnosed as having alopecia areata (AA). Within three months, AA progressed to complete loss of all body hair (alopecia universalis). Current literature rarely connects alemtuzumab with the onset of alopecia of autoimmune origin. Here, we report a little-noticed autoimmune disease affecting the skin, very likely being associated with alemtuzumab. We emphasize the necessity of careful clinical surveillance of alemtuzumab-treated patients for yet undescribed autoimmune diseases.